Swimming ability, perceived competence and perceived risk among young adults - Stallman, R. K.; Dahl, D.; Moran, K.; Kjendlie, P. L. (Biomechanics and Medicine in Swimming XI, 2010)
Why do swimmers get into trouble? Do they over estimate their ability, underestimate the risk, both? Eighty one (n = 81) university physical education students completed a questionnaire and performed seven practical swimming tests. The questionnaire covered a) perception of ability, b) perception of difficulty in open water and c) perception of risk. Gender differences were tested by the Mann-Whitney U test. The women out performed the men on 4 of 7 practical tests. There were few gender differences in perceived competence. The women were highly confident about floating in open water while the men were certain they could not do the same. The men predicted 100% success on surface diving to the bottom of the pool (4m) while the women were less certain (88%). On 5 scenarios depicting risk, there were no gender differences.